AN INVESTIGATION INTO LOSS AND GAIN IN MEANING OF CLASSIC REFERENCE OF TRUYEN KIEU IN ITS ENGLISH TRANSLATION VERSION - Trà Thị Thùy Dung (2015)
Introduction; Literature review and theoretical background; Research design and Methodology; ...